Aerobic bacteria and fungi from skin lesions of fish in Khartoum state - Ibrahim, Walaa Hassan; Nimir, Abdel-Hafeez Hassan; El-Sanousi, Suleiman Mohamed; Shuaib, Yassir Adam (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This cross-sectional study was conducted from April to July 2014 in Khartoum state, the Sudan, to investigate aerobic bacteria and fungi of skin lesions of fish in 3 different areas in Khartoum. Material and methods: A total of 50 samples were collected from the skin lesions of different types of fish including Synodontis species (n=17), Tilapia niloticus (n=15), Labeo niloticus (n=10), Hydrocynus species (n=4), and Clarias species (n=4). Liquid, semi-solid, and solid culture media like nutrient broth, blood agar, MacConkey agar, sabouraud dextrose agar (SDA), and Simmon's citrate medium were used for the isolation and identification of bacteria and fungi. Besides, Gram staining and biochemical characterization were also conducted. Results: Culturing of the collected samples revealed growth of bacteria from all (100%), and growth of fungi could be found from 32% samples. A number of 188 bacteria were isolated, mainly Staphylococcus species, Bacillus species, Aeromonas species, Pseudomonas species, and Vibrio species. Besides, 16 fungi could be identified containing Aspergillus niger, A. flavus, A. fumigatus, and Phycomycete. Conclusion: Fishes with skin lesions are harboring many pathogenic bacteria and fungi and may act as a source of zoonotic infections and can transmit several pathogens to workers in fish industry and consumers. Therefore, thorough and strict routine inspection of fish is recommended to ensure safety and that there are no serious risks to consumers. http://doi.org/10.5455/javar.2016.c176